2020
DOI: 10.3390/antiox9030192
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Inflammatory and Antioxidant Properties of the Ethanol Extract of Clerodendrum Cyrtophyllum Turcz in Copper Sulfate-Induced Inflammation in Zebrafish

Abstract: Oxidative stress and inflammation are commonly present in many chronic diseases. These responses are closely related to pathophysiological processes. The inflammatory process can induce oxidative stress and vice versa through the activation of multiple pathways. Therefore, agents with antioxidant and/or anti-inflammatory activities are very useful in the treatment of many pathologies. Clerodendrum cyrthophyllum Turcz, a plant belonging to the Verbenaceae family, is used in Vietnamese traditional medicine for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 33 publications
(63 reference statements)
0
22
0
3
Order By: Relevance
“…Inflammation plays a critical role in the progression of CuSO 4 exposure-induced toxic effects ( 54 56 ). In the present study, our results showed that CuSO 4 exposure significantly upregulated the expression of IL-1β, TNF-α, and IL-6 proteins and mRNAs in the kidney tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation plays a critical role in the progression of CuSO 4 exposure-induced toxic effects ( 54 56 ). In the present study, our results showed that CuSO 4 exposure significantly upregulated the expression of IL-1β, TNF-α, and IL-6 proteins and mRNAs in the kidney tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to copper can cause injuries to superficial tissues, in particular to the hair cells of the zebrafish lateral line, followed by an acute inflammatory response [49,50]. Thus, treatment of zebrafish embryos/larvae with copper is today commonly used to analyze inflammatory response [65,66]. Since cyanobacterial EPS can bind dissolved heavy metal bipositive cations such as Cu 2+ or Pb 2+ [51], Phormidium EPS was applied to copper-treated larvae only after multiple washes.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative PCR Total RNA extraction, DNase and reverse transcription Total RNA extraction, DNase and reverse transcription were carried out as described in previous our study (Nguyen et al, 2020a) using Trizol Reagent solution (Ambion, Thermofisher Scientific), DNA-free™ DNA Removal Kit-Invitrogen and the RevertAid RT kit (Thermo Scientific).…”
Section: Analysis Of Mrna Expression By Quantitative Polymerase Chainmentioning
confidence: 99%
“…Clerodendrum cyrtophyllum Turcz (Lamiaceae), a medicinal plant, is widely used in traditional medicine of many Asian countries such as China, India, Japan, Korea, Thailand, and Vietnam for the treatment of colds, high fever, migraines, hypertension, enteritis, dyspepsia, inflammation of the throat, rheumatic arthritis, fever, jaundice, leukorrhea, syphilis, and typhoid (Kar et al, 2014;Zhou et al, 2013). Several therapeutic and pharmacological properties of Clerodendrum cyrtophyllum Turcz have recently been reported such as antioxidant, anti-inflammatory (Nguyen et al, 2020a(Nguyen et al, , 2020b, and anticancer (Cheng et al, 2001) activities. Despite their frequent use, studies on its toxicity and its effects on reproductive tissues or embryos are currently unknown.…”
Section: Introductionmentioning
confidence: 99%